Powerful cell wall biomass degradation enzymatic system from saprotrophic Aspergillus fumigatus - Lige Tong; Yunaying Li; Xinke Lou; Bin Wang; Cheng Jin; Wenxia Fang (The Cell Surface, 2024)
Cell wall biomass, Earth’s most abundant natural resource, holds significant potential for sustainable biofuel production. Composed of cellulose, hemicellulose, lignin, pectin, and other polymers, the plant cell wall provides essential structural support to diverse organisms in nature. In contrast, non-plant species like insects, crustaceans, and fungi rely on chitin as their primary structural polysaccharide. The saprophytic fungus Aspergillus fumigatus has been widely recognized for its adaptability to various environmental conditions. It achieves this by secreting different cell wall biomass degradation enzymes to obtain essential nutrients. This review compiles a comprehensive collection of cell wall degradation enzymes derived from A. fumigatus, including cellulases, hemicellulases, various chitin degradation enzymes, and other polymer degradation enzymes. Notably, these enzymes exhibit biochemical characteristics such as temperature tolerance or acid adaptability, indicating their potential applications across a spectrum of industries.